TLR3 Ligand Poly(I:C) Exerts Distinct Actions in Synovial Fibroblasts When Delivered by Extracellular Vesicles - Frank-Bertoncelj, Mojca; Pisetsky, David S.; Kolling, Christoph; Michel, Beat A.; Gay, Renate E.; Jüngel, Astrid; Gay, Steffen (Frontiers in Immunology, 2018)
Extracellular vesicles (EV) can modulate the responses of cells to Toll-like receptor (TLR) ligation; conversely, TLR ligands such as double stranded RNA (dsRNA) can enhance the release of EV and influence of the composition and functions of EV cargos. Inflamed synovial joints in rheumatoid arthritis (RA) are rich in EV and extracellular RNA; besides, RNA released from necrotic synovial fluid cells can activate the TLR3 signaling in synovial fibroblasts from patients with RA. Since EV occur prominently in synovial joints in RA and may contribute to the pathogenesis, we questioned whether EV can interact with dsRNA, a TLR3 ligand, and modify its actions in arthritis. We have used as model the effects on rheumatoid arthritis synovial fibroblasts, of EV released from monocyte U937 cells and peripheral blood mononuclear cells upon stimulation with Poly(I:C), a synthetic analogue of dsRNA. We show that EV released from unstimulated cells and Poly(I:C)-stimulated U937 cells [Poly(I:C) EV] differ in size but bind similar amounts of Annexin V and express comparable levels of MAC-1, the receptor for dsRNA, on the vesicular membranes. Specifically, Poly(I:C) EV contain or associate with Poly(I:C) and at least partially protect Poly(I:C) from RNAse III degradation. Poly(I:C) EV shuttle Poly(I:C) to synovial fibroblasts and reproduce the pro-inflammatory and antiviral gene responses of synovial fibroblasts to direct stimulation with Poly(I:C). Poly (I:C) EV, however, halt the death receptor-induced apoptosis in synovial fibroblasts, thereby inverting the pro-apoptotic nature of Poly(I:C). These pro-survival effects sharply contrast with the high toxicity of cationic liposome-delivered Poly(I:C) and may reflect the route of Poly(I:C) delivery via EV or the fine-tuning of Poly(I:C) actions by molecular cargo in EV. The demonstration that EV may safeguard extracellular dsRNA and allow dsRNA to exert anti-apoptotic effects on synovial fibroblasts highlights the potential of EV to amplify the pathogenicity of dsRNA in arthritis beyond inflammation (by concurrently enhancing the expansion of the invasive synovial stroma).